In vitro anticancer property of a novel thalidomide analogue through inhibition of NF-κB activation in HL-60 cells - Li Min; Sun Wan; Yang Ya-ping; Xu Bo; Yi Wen-yuan; Ma Yan-xia; Li Zhong-jun; Cui Jing-rong (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the anticancer property and possible mechanism of action of a novel sugar-substituted thalidomide derivative (STA-35) on HL-60 cells in vitro. Methods: TNF-α-induced NF-κB activation was determined using a reporter gene assay. The MTT assay was used to measure cytotoxicity of the compound. The appearance of apoptotic Sub-G1 cells was detected by flow cytometry analysis. PARP cleavage and protein expression of NF-κB p65 and its inhibitor IκB were viewed by Western blotting. Results: STA-35 (1–20 μmol/L) suppressed TNF-α-induced NF-κB activation in transfected cells (HEK293/pNiFty-SEAP) in a dose- (1–20 μmol/L) and time-dependent (0–48 h) manner. It was also shown that STA-35 exerted a dose-dependent inhibitory effect on HL-60 cell proliferation with an IC50 value of 9.05 μmol/L. In addition, STA-35 induced apoptosis in HL-60 cells, as indicated by the appearance of a Sub-G1 peak in the cell cycle distribution, as well as poly ADP-ribose polymerase (PARP) cleavage. Subsequently, both NF-κB p65 and its inhibitor IκB gradually accumulated in cytoplasmic extracts in a dose- and time-dependent manner, indicating the blockage of NF-κB translocation induced by TNF-α from the cytoplasm to the nucleus. Conclusion: A novel sugar-substituted thalidomide derivative, STA-35, is potent toward HL-60 cells in vitro and induces apoptosis by the suppression of NF-κB activation.